EFEK TERAPI MUSIK UNTUK MENURUNKAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI DESA TARAMAN SRAGEN JAWA TENGAH - Diyono, Diyono; Mawarni, Putri (KOSALA : Jurnal Ilmu Kesehatan, 2015)
Background: Hypertension is often called the "silent killer" (killer stealth), because often people with hypertension chronically ill without experiencing clinically overt disease. The prevalence of hypertension in Indonesia reached 31.7% of the population aged 18 years and above. Of that amount, 60% of hypertension patients have complications of stroke. While the rest of developing heart disease, kidney failure, and blindness. Hypertension is the third leading cause of death after stroke and tuberculosis, accounted for 6.8% of the proportion of causes of death in all age groups in Indonesia. Management of hypertension can be nonpharmacological therapy such is music therapy Objective: (1) determine the classification of hypertension in the village Taraman Sragen (2) determine the blood pressure in patients with hypertension in the village Taraman Sragen before given music therapy. (3) determine the blood pressure in patients with hypertension in the Village Sragen Taraman after the given music therapy (4) the effect of music therapy on reduction of blood pressure in patients with hypertension.Methode: This type of research is analytic quasi - experimental design Research Subjects: The study population was patients with hypertension in the village of Taraman Sragen. A large population of 33 people who suffer from hypertension. Be obtained through the total sampling technique respondents who met the inclusion criteria as much as 20 respondents. Effect of music therapy was analysed by Paired T-Test with SPSS18.Results: (1) Classification of systolic hypertension is lightweight category 75%, the category was 25%, and the average  category mild hypertension (2) The classification of hypertensive diastolic including mild 20%, moderate 55%, severe 25%, and the average including moderate hypertension category (3) blood pressure before being given music therapy for systolic average 150.5 categorized as mild and diastolic average 100.5 including medium category (4) systolic blood pressure after being given music therapy average 130 (high normal category) and for diastolic average 88 including the normal category (5) Results of statistical test with Paired T-Test showed that a significant effect of music therapy in decrease or reduced sistolic and diastolic blood pressure (sig = 0,000) Conclusion: Music therapy significant influence in decrease blood pressure (sig = 0,000).Keywords: Music Therapy and Blood Pressure